2019
DOI: 10.1016/j.avsg.2018.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcome of Carotid Endarterectomy in Patients with Carotid Artery Stenosis

Abstract: Background: Carotid endarterectomy (CEA) is deemed to restore the blood flow of the carotid and ophthalmic arteries in patients with carotid artery stenosis. However, specific changes in visual function before and after CEA are not well understood; hence, this observational study aimed to investigate the functional and structural changes in vision after CEA in those patients. Methods: Patients with severe carotid artery stenosis (>70% with standard carotid duplex scanning or arteriography) scheduled to undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
2
13
1
Order By: Relevance
“…ese data are in concordance with our previous investigation documenting that CEA for asymptomatic carotid artery stenosis is reproducibly associated with improvement of retinal function [23,31]. In contrast, Rabina et al, based on a group of 8 patients with unilateral severe ICAS undergoing carotid endarterectomy, did not find any significant differences in SFCT between 6 and 14 months after surgery.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ese data are in concordance with our previous investigation documenting that CEA for asymptomatic carotid artery stenosis is reproducibly associated with improvement of retinal function [23,31]. In contrast, Rabina et al, based on a group of 8 patients with unilateral severe ICAS undergoing carotid endarterectomy, did not find any significant differences in SFCT between 6 and 14 months after surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Insufficient blood supply to the eye due to internal carotid artery stenosis (ICAS) may manifest as acute or chronic ischaemic symptoms [17][18][19][20]. Carotid endarterectomy (CEA) is considered an effective therapeutic method for improving cerebral and ocular circulation [21][22][23]. Moreover, improvements in blood flow within the ophthalmic, central retinal, and posterior ciliary arteries as well as in the retinal and choroidal circulation have been documented [21,22,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that significant stenosis causing disruption of carotid blood flow could impact the blood supply to the retina. Improved retinal blood flow assessed by optical coherence tomography angiography has been reported in participants with carotid stenosis > 70% after carotid endarterectomy [48], and there is evidence that vision improves after carotid endarterectomy [49]. However, as some studies found that IMT was independently associated with DR, more than one mechanism is likely with a combination of common soil and direct relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of carotid endarterectomy on ocular manifestations of CAS has been widely studied in the recent years. Yan et al observed an improvement in both subjective and objective visual function (such as visual acuity, static and kinetic visual fields, visually evoked potentials and electroretinographic parameters) in patients after surgical treatment [143]. However, no changes were detected regarding the RNFL thickness [143].…”
Section: Effects Of Cas and Its Surgical Treatment (Carotid Endarterectomy) On The Retinamentioning
confidence: 99%
“…Yan et al observed an improvement in both subjective and objective visual function (such as visual acuity, static and kinetic visual fields, visually evoked potentials and electroretinographic parameters) in patients after surgical treatment [143]. However, no changes were detected regarding the RNFL thickness [143]. In contrast, Guclu et al reported a statistically significant decrease in peripapillary RNFL thickness in the superior quadrant following surgery [144].…”
Section: Effects Of Cas and Its Surgical Treatment (Carotid Endarterectomy) On The Retinamentioning
confidence: 99%